Perancangan Sistem Informasi Manajemen Koperasi Berbasis Website Dengan Metode Prototype Berdasarkan Standar ISO/IEC 25010 - Ahyat Musyawwa; Maulida Alfia Syifa; Chairul Anwar (Journal of Information Systems and Business Technology, 2026)
Digital transformation in the era of the industrial revolution 4.0 requires organizations to adopt information technology to maintain operational efficiency and accurate decision-making. PT Solusindo, as an entity managing residential neighborhoods and community cooperatives, currently still faces significant obstacles due to the use of manual and semi-digital management methods in the management of Environmental Management Fees (IPL) and cooperative administration. These problems impact the risk of data corruption, delays in financial reporting, and low transparency, which triggers a decline in community trust. This study aims to design an integrated website-based cooperative management information system to automate transaction recording and provide open access to information for all stakeholders. System development was carried out using a prototype method to ensure the suitability of functional features through iterations and direct feedback from users. To ensure software quality, testing was conducted based on the international standard ISO/IEC 25010, which covers aspects of functionality, performance efficiency, and usability. The results of this study are projected to be able to ensure the accuracy of centralized data, improve the work efficiency of administrative staff, and rebuild community trust through a transparent and accountable reporting system.